High efficiency and broad bandwidth grating coupler between nanophotonic waveguide and fibre - 朱宇 徐学俊 李智勇 周亮 韩伟华 樊中朝 俞育德 余金中 (Chinese physics B, 2010)
A high efficiency and broad bandwidth grating coupler between a silicon-on-insulator （SOI） nanophotonic waveguide and fibre is designed and fabricated. Coupling efficiencies of 46% and 25% at a wavelength of 1.55um are achieved by simulation and experiment, respectively. An optical 3 dB bandwidth of 45 mn from 1530 nm to 1575 nm is also obtained in experin, ent. Numerical calculation shows that a tolerance to fabrication error of 10 nm in etch depth is achievable. The measurement results indicate that the alignment error of 112 um results in less than 1 dB additional coupling loss.